The lens of Print Media Journalism in “Op-ed” and “Editorial” section at The Daily Observer - Hasan, Md. Mahedi (Brac University, 2021)
This internship report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Arts in English, 2021.